The Influence of Perceived Risk on Participation in Outdoor Education Activities by Pre-Teen Age Schoolchildren in New Zealand - Jones, Mark Lewis (Auckland University of Technology, 2011)
Outdoor education is a formal part of the New Zealand school curriculum under the auspices of Education Outside the Classroom (EOTC). Anecdotally New Zealand parents and teachers are becoming more risk averse as a result of high profile fatalities associated with outdoor recreation. Consequently, it is important to understand how risk is perceived by parents and teachers and what influence it may be having on participation rates and programming for outdoor education. Views on perceived risk were gained from teachers with responsibilities related to EOTC (n=276) and parents from primary and intermediate school boards of trustees (n=534) via an online self-reply questionnaire. Eleven semi-structured telephone interviews were also conducted with key informants from providers of outdoor education to these schools. Higher levels of the risk of serious harm perceived by teachers (moderate risk compared with low risk for parents) are likely to be related to a greater emphasis on and increased discourse around safety in EOTC and their responsibility for the safety of children in their school when undertaking outdoor education activities. Accidents and fatalities reported in the media increased parental anxiety, but only resulted in isolated cases of parents preventing their children from participating in outdoor education programmes. A small proportion of schools (8%) responded to accidents and fatalities reported in the media by reducing outdoor education programmes. Aversion to water activities in outdoor education by some schools was shown and is likely symptomatic of high perceived risk of the aquatic environment. Outdoor activities such as canoe sports on rivers and climbing/abseiling from cliffs were perceived to be the most risky activities by both parents and teachers. There were isolated cases of parents, and sometimes, whole schools cancelling outdoor education trips for children. These were seized on by the media as documented proof of “wrapping children in cotton wool”, “paranoid parenting” and other phenomenon implying parents or teachers are risk averse to an unhealthy degree. This study has provided empirical data showing that the vast majority of parents and teachers do not respond in a risk averse way as a result of high profile fatalities associated with outdoor recreation.
Keywords: Schoolchildren; Outdoor recreation; Outdoor education; EOTC